Nutrient Composition and Growth of Yellow Mealworm (Tenebrio molitor) at Different Ages and Stages of the Life Cycle - Odunayo A. Toviho; Péter Bársony (Agriculture, 2022)
The nutrient composition of yellow mealworm (YM) Tenebrio molitor varies based on the stages of the life cycle, the rearing conditions, and the feeding substrate. This study monitored the growth of yellow mealworm larvae at 8, 10, and 12 weeks of age, separating samples into large-sized and small-sized insects. During the experiment, we measured the nutrient composition: dry matter (DM), crude protein (CP), crude fat (CF), crude fibre, chitin, crude ash, and nitrogen free extract (NFE) of YM at different age groups and sizes. We measured the nutrient composition of the pre-moult, moult, cuticle, and pupae as well. The results show that there is no significant difference between the compositions of the different age groups, but larger-sized individuals had a higher DM and crude fibre and lower chitin and NFE than the smaller sizes. The pre-moult and moult stages showed no significant difference in nutrient composition. Although the cuticle had a high DM (97.5%), that did not cause any significant difference between the DM of the moult and pre-moult, because it is only a negligible part of the total wet weight. With the increased DM, the crude protein content and the chitin content, fibre, ash content, and NFE increased, while the fat content decreased. The DM, CF, and chitin contents of pupae are significantly lower than those of the pre-moult and moult stages. Our results show that it is the size and not the age that has a positive effect on the nutrient composition of YM.